How Do Firms Change Investments Based on MD&A Disclosures of Peer Firms? - Cho, Hyunkwon; Muslu, Volkan (The Accounting Review, 2021)
ABSTRACT We show that a firm's one-year-ahead capital investments and inventory increase (decrease) when peer firms' Management Discussion and Analysis (MD&A) narratives become more optimistic (pessimistic). This finding is driven by firms that access peer firms' 10-K filings within seven days of their filing date, and remains after controlling for other determinants of a firm's investments as well as economic connections between the firm and peer firms. Moreover, a firm's investment response varies based on content in peer firms' MD&A narratives. For instance, a firm makes more (less) capital investments when peer firms become more optimistic in their narratives that discuss the industry and investments (competition). Our findings provide broad insights on the information content and proprietary costs of MD&A disclosures. Data Availability: All non-textual data are available from sources identified in the text. Textual data generated by this study are available upon request. JEL Classifications: L1; D25.